Dynamic Modeling of Electric Power on Light UAV - AN Siqi; LIU Xiaofeng; HOU Kuanxin; XU Xingchen (Journal of Harbin University of Science and Technology)
Focused on UAV(unmanned aerial vehicle) equipped electric power plant composed by Electric speed controllers, brushless DC motors and fixpitched propellers, a modeling method combined deduction with identification is studied Firstly, in consideration of typical flight modes, the dynamic model of electric power was deduced based on component characteristics, and the model shows a nonlinear differential formula with a linear term and a nonlinear term Secondly, an identification method is given To avoid the aerodynamical nonlinear term, the propeller was replaced by a specialized discshaped coder with equivalent inertial moment, and the linear parameters were identified directly through output response Afterwards, the nonlinear parameter was identified by static inand output signals Finally the method of dynamic modeling is proved to be effective on a ground test unit